The Influence of Leadership and Motivation on the Performance of Gowa Regency Trade and Industry Service Employees - Mirnawati; Dg Maklassa; Ismail Rasulong (Yayasan Amerta Insan Unggul, 2024)
This study examines the influence of leadership and motivation on the performance of employees at the Trade and Industry Office of Gowa Regency, Indonesia. Effective leadership and employee motivation are crucial factors in enhancing organizational performance and productivity. This quantitative research involved 35 employees as respondents selected through a census sampling technique. Data were collected using structured questionnaires and analyzed through validity and reliability testing, classical assumption tests, multiple linear regression, and hypothesis testing. The results reveal that leadership has a positive and significant effect on employee performance with a significance value of 0.000 (t-count 5.246 > t-table 1.692). Similarly, motivation also has a positive and significant effect on performance with a significance value of 0.000 (t-count 3.897 > t-table 1.692). These findings indicate that strong leadership and high motivation contribute significantly to improving employee performance. The results suggest that leaders should adopt participatory and motivational approaches to strengthen employees’ sense of responsibility and commitment toward achieving organizational goals. This study contributes to the understanding of human resource management practices in public organizations and offers practical implications for enhancing leadership and motivation in government institutions.